Proposed B2B Marketing Strategy to Strengthen Industrial Customer Relationship: A Commitment-Trust Theory Approach at PLN UID East Java - Bayu Aswenda (Green Publisher Indonesia, 2026)
PT PLN (Persero) UID East Java, the state utility serving Indonesia's second-largest industrial hub, faces an emerging challenge this study terms partial defection: customers do not switch away from PLN, but progressively reduce their share of wallet via rooftop photovoltaic (Rooftop PV) self-generation while staying grid-connected. Industrial Rooftop PV capacity grew roughly 200-fold, from 0.80 MWp (2020) to 163.82 MWp (April 2026), as carbon-border pressures and falling renewable costs reshape expectations toward integrated green solutions. This study proposes a B2B marketing strategy grounded in Commitment-Trust Theory Morgan & Hunt, the Key Mediating Variable (KMV) model examining PLN's internal-external conditions, four antecedents' influence on Trust and Commitment, their effect on Propensity to Leave and Cooperation, and the resulting strategy. PLS-SEM tested nine hypotheses on 300 industrial respondents (24 HV, 276 MV), followed by Importance-Performance Map Analysis (IPMA), with frameworks converged through a SWOT/TOWS matrix. All nine hypotheses were supported; Communication was the strongest antecedent of Trust (β = 0.460), and Relationship Commitment the strongest determinant reducing Propensity to Leave (β = −0.577). IPMA identified Shared Values and Relationship Termination Cost as Tier 1 leverage, while beyond-kWh rivalry was HIGH and rising across four competitor categories. The proposed strategy synthesizes four Strategic Thrusts—Repositioning as Energy Transition Partner, PLN Group Orchestration, Digital-First B2B Infrastructure, and PAE Upskilling—decomposed into twelve sub-initiatives across a 0–24-month roadmap. The study validates KMV in a regulated-utility developing-country context, integrates IPMA as a B2B prioritization tool.